Abducting Children Abroad: Gender, Power, and Transnational Mobility in Immigrant Family Conflicts - Liversage, Anika (Violence against women, 2022)
Utilizing life story interviews of immigrant women whose children were abducted by abusive (ex-)husbands, the article unpacks a three-part pattern of transnational mobility: first, husbands apply strategies of coercive control to dominate wives in Denmark; second, wives draw on Scandinavian “woman-friendly” state support to challenge men and seek divorce; and third, men try to regain control through abducting children to the Middle East, seeking to blackmail mothers into leaving Denmark and resubmitting themselves to male control. While some wives accede to their husband’s demands, others skillfully manage to “re-abduct” children back to Denmark, thereby belying the trope of the victimized immigrant woman.